Staged Entry to Self-Employment - And After? - Kritskaya, Lidia; Kolvereid, Lars (Senate Hall, 2021)
Some novice business owners enter directly to self-employment from paid employment. Others start as hybrid entrepreneurs by combining business ownership with salaried employment and become self-employed later, using a staged entry mode to self-employment. The purpose of this study is to investigate the relationship between the direct versus staged entry mode to self-employment and the duration of self-employment as well as the duration as hybrid entrepreneurs after the exit from self-employment. Using commitment theory, we derive hypotheses stating that staged entry to self-employment is associated with (1) shorter duration as self-employed, and (2) longer duration as hybrid entrepreneurs after the exit from self-employment. The hypotheses are tested using Propensity Score Matching. In particular, we create matched samples of self-employed incorporated entrepreneurs who used staged and direct entry to self-employment in Norway. The findings support the hypotheses. Implications for practice and research are spelled out.
Keywords: novice business owners|hybrid entrepreneurship|self-employment|commitment|duration